The strategic planning development: A case study of Koperasi Permodalan Kelantan Berhad / Norhazrini Mamat Yusof - Mamat Yusof, Norhazrini (Faculty of Business and Management, 2008)
This study is to develop a strategy and offer strategic formulations and recommendations. The research context is on analyzing the company's external and internal environments. This study is collaboration of an analysis of company's strengths, weaknesses, opportunities and threats and matching strategies necessary for the selection of the appropriate strategic activities. Several interviews and focus groups were conducted at KPKB to gain insights into KPKB's competitive advantages and disadvantages. An analysis of the strengths, weaknesses, opportunities and threats of KPKB revealed several competitive advantages that the company possesses over sit rivals as well as some areas of weakness that can be improved The methods used in this study are both primary and secondary data. Thus, using SWOT analysis, the matching strategies were developed from the matching strategies and SWOT analysis was used to develop strategic business plan for KPKB together with a set of recommendations in very specific issues, which the company should address. Finally, there are specific strategies develop. This study includes a proposed expansion plan (based on a strategic analysis conducted for KPKB) and teaching case study for use in management of KPKB.